1989
DOI: 10.1002/jbmr.5650040506
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive axial and peripheral assessment of bone mineral content: A comparison between osteoporotic women and normal subjects

Abstract: We compared different methods of bone densitometry in women with spinal osteoporosis and normal subjects to assess their discriminatory capability. The methods used included: quantitative computed tomography of the spine (QCT) specified as to trabecular (QCTtrab) and cortical bone (QCTcort), dual-photon absorptiometry of the spine (DPAspine), single-photon absorptiometry of the distal and proximal forearm (SPAdist and SPAprox), and quantitative roentgen microdensitometry of the phalanx (QMD). A total of 25 pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…A fracture is commonly classified to be osteoporotic if it arises in a patient over 50 and the BMD of the fracture site is sufficiently low (Kanis et al 2001). DEXA is the preferred technology for quantifying BMD (Cummings et al 2002;Leib et al 2004), but other diagnostic tools, including quantitative computed tomography (QCT), absorptiometry, quantitative roentgen micro-densitometry and quantitative ultrasound (QUS), may provide more accurate measures of BMD (Richardson et al 1985;van Berkum et al 1989). Nonetheless, BMD is a poor predictor of fracture risk as changes in bone mass alone do not fully explain susceptibility to bone fracture; for example, only 10-53% of bone fractures that occur in female postmenopausal patients over the age of 65 can be attributed to a BMD level low enough (i.e.…”
Section: Bone Mass During Osteoporosismentioning
confidence: 99%
“…A fracture is commonly classified to be osteoporotic if it arises in a patient over 50 and the BMD of the fracture site is sufficiently low (Kanis et al 2001). DEXA is the preferred technology for quantifying BMD (Cummings et al 2002;Leib et al 2004), but other diagnostic tools, including quantitative computed tomography (QCT), absorptiometry, quantitative roentgen micro-densitometry and quantitative ultrasound (QUS), may provide more accurate measures of BMD (Richardson et al 1985;van Berkum et al 1989). Nonetheless, BMD is a poor predictor of fracture risk as changes in bone mass alone do not fully explain susceptibility to bone fracture; for example, only 10-53% of bone fractures that occur in female postmenopausal patients over the age of 65 can be attributed to a BMD level low enough (i.e.…”
Section: Bone Mass During Osteoporosismentioning
confidence: 99%
“…Therefore, measurement of bone mineral density is an important tool in the diagnostic evaluation of patients suspected of having or suffering from osteoporosis or other skeletal disorders [ 21 ]. In human medicine, it is preferable to measure only trabecular bone because it is thought to be eight times more sensitive to hormonal deficiencies and metabolic disease than cortical bone [ 6 16 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…In numerous studies the highest diagnostic sensitivity was found for QCT of the lumbar spine, regarded by many researchers as the diagnostic gold standard (Grampp et al , 2001aPacifi ci et al 1990;Reinbold et al 1986;van Berkum et al 1989;Yu et al 1995). In numerous studies the highest diagnostic sensitivity was found for QCT of the lumbar spine, regarded by many researchers as the diagnostic gold standard (Grampp et al , 2001aPacifi ci et al 1990;Reinbold et al 1986;van Berkum et al 1989;Yu et al 1995).…”
Section: Choice Of Techniquementioning
confidence: 99%